GROT-transport från norra till södra Sverige - Johansson, Sara; Pettersson, Tobias (2011)
The European Council agreed in 2008 on a climate and energy package to combat global warming. This package is valid for each EU member country and means that greenhouse gas emissions must fall by at least 20% and the EU's energy use to 20%, consisting of Renewable Energy in 2020. The Swedish Government has set stringent climate and energy with the intention to set an example for the rest of Europe. For example, renewable energy sources account for at least 50% of energy use and our climate emissions to fall by 40% by 2020. A combination of these goals and a steadily rising oil price has led to an increased demand for wood fuel in the form of such branches and tops. The problem in Sweden is that the availability of logging residue is highest where demand is lowest. The question is whether it is profitable to transport the wood fuel from the inner Norrland to a power plant in southern Sweden? Based on a requested amount of energy was a pine and a spruce-dominated catchment chosen. Then the variable costs of transportation of merchandise from the offshoot to the terminal, for processing in the form of pelleting or chipping, as well as for rail transport from the terminal to the power plant was calculated. The final result showed that there may be an economic viability of transporting wood fuel from northern Sweden to Gothenburg.